Integrated Recruitment And Continuous Training Determine Employee Productivity: Rekrutmen Terintegrasi Dan Pelatihan Berkelanjutan Menentukan Produktivitas Karyawan - Adylla Fitria Maharani; Anisah Nur Azizah; Erfinda Maulidiah; Lutfianti Wulandari; Muhammad Yani (International Consortium of Education and Culture Research Studies, 2024)
General Background Human resources represent a critical component determining organizational survival and operational success within a highly competitive global business environment. Specific Background Within the sugar industry, companies such as PT PG Candi Baru Sidoarjo face significant workforce challenges, including suboptimal hiring processes and insufficient skills development, which hinder operational efficiency. Knowledge Gap Despite the recognized importance of human capital, there is a lack of qualitative exploration regarding how the precise integration of targeted hiring and ongoing competency development functions within the specific technological transitions of the sugar manufacturing sector. Aims This study explores the application and outcomes of integrated talent acquisition and ongoing skill development strategies on worker performance at PT PG Candi Baru Sidoarjo. Results Descriptive qualitative analysis utilizing interviews and observations reveals that combining internal and external hiring with project-centric learning and mentoring significantly accelerates task completion, minimizes errors, and reduces staff turnover. Novelty This research provides empirical qualitative evidence on the synergistic mechanism of combining precise talent acquisition with modern, project-centric learning to specifically address technological adaptation needs in the sugar industry. Implications Organizations must synergize their human resource practices by aligning targeted candidate selection with ongoing capability development and mentoring to secure long-term operational sustainability and competitiveness. Highlights: Talent acquisition strategies successfully lower staff turnover and retain workers. Project-centric learning accelerates task completion while minimizing operational errors. Internal mentoring systems build a sustainable culture of workplace competency development. Keywords: Human Resource Management, Talent Acquisition, Skill Development, Work Efficiency, Sugar Industry